The institutionalized Buen Vivir: a new hegemonic political paradigm for Ecuador - Benalcazar, Patricio Carpio; de La Rosa, Francisco Javier Ullan (Revista Brasileira de Política Internacional, 2021)
Buen Vivir has recently emerged in Latin America as an alternative societal model to the historical liberal (or neoliberal) and Marxist ones. The article focuses on its Ecuadorian variant and, more specifically, the institutionalized version embodied in the 2008 Constitution and the policies of the Citizens' Revolution governments. This version is the particular result of the convergence of three different currents and has become the hegemonic ideology in the country. The article describes its main thematic axes and appraises its originality, as well as the theoretical and practical contributions. Keywords: Buen vivir, Sumak Kawsay, post-development, Ecuador, Citizens' Revolution, XXI-century socialism.